Europeanization subverted? The European Union's promotion of good governance and the fight against corruption in the Southern Caucasus - Börzel, Tanja A.; Pamuk; Yasemin (2011)
Abstract: In order to foster peace, stability and prosperity in its near abroad, the European Union has invoked the European Neighbourhood Policy that seeks to transform the domestic structures of the Newly Independent States in the post-Soviet space thus building a “ring of friends” that share European norms and principles of democracy, rule of the law, market economy, and good governance. Empirical evidence, however, suggests that the EU’s capacity to hit across its borders and to realize its reform agenda seems limited. Moreover, most neighborhood countries appear to be stuck in transition and suffer from serious problems of both weak state capacity and defect democracy. Hence, EU efforts may also bear the danger of unintended and negative effects on the domestic structures of states, as its policies and institutions do not only empower liberal reform coalitions, to the extent that they exist in the first place, but can also bolster the power of incumbent authoritarian and corrupt elites